2012
DOI: 10.1134/s0023158412020085
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the C-H bonds of methyl hexanoate toward the tert-butylperoxy radical

Abstract: 155Carboxylic acid esters resulting from the liquid phase oxidation of hydrocarbons and their oxygen derivatives [1,2] can enter into free radical chain pro cesses involving both the acyl and alkoxyl moieties [1,3,4]. The electron withdrawing functional group affects the mechanisms of formation and transforma tion of the intermediates (peroxyl radicals and hydro peroxides) and also the reactivity of the C-H bonds nearest to this functional group [1,3,4]. It was shown for the reactions of tert butylperoxy radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…37 It is found that recombination of peroxyl radicals without chain termination also takes place during oxidation of aliphatic esters. 40 In studies of the recombination of peroxyl radicals, including radicals formed during the oxidation of esters, an assumption was made that the Russell mechanism (Scheme 5) with six-membered transition state 12 is too simplifi ed, but it rather adequately refl ects the nature of the transformations of peroxyl radicals. 12,13,16,64…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…37 It is found that recombination of peroxyl radicals without chain termination also takes place during oxidation of aliphatic esters. 40 In studies of the recombination of peroxyl radicals, including radicals formed during the oxidation of esters, an assumption was made that the Russell mechanism (Scheme 5) with six-membered transition state 12 is too simplifi ed, but it rather adequately refl ects the nature of the transformations of peroxyl radicals. 12,13,16,64…”
Section: Methodsmentioning
confidence: 99%
“…Now we can consider the data on the kinetics of accumulation of primary products of methyl hexanoate oxidation initiated with cumene hydroperoxide at 373 К (Fig. 1) 40 and cyclohexyl acetate oxidation initiated with azobisisobutyronitrile at 333 К (Fig. 2) 42 together with the data on the composition of products of neopentyl heptano- (7), and hexanoic acid (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Опыт ГЖХ-анализа гидропероксидных продуктов окисления спиртов [7], кетонов [8], сложных эфиров [9,10] и карбоновых кислот [11] с использованием насадочных хроматографических колонок показывает, что присутствие ТФФ и ТФФО в пробах приводит лишь к необходимости регулярного проведения процедуры стабилизации хроматографической колонки при температурах выше рабочей температуры колонки для удаления из нее абсорбированных ТФФ и ТФФО. В ГЖХанализе образцов, содержащих ТФФ и ТФФО с использованием капиллярных хроматографических колонок, кроме необходимости регулярной стабилизации колонки возникает еще ряд проблем.…”
unclassified